La interleuquina-8 como molécula clave en el periodonto - Medina, María Eugenia; Patiño, Pablo; Sierra, Luz Inés (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Periodontal disease is the result of the interaction of periodontal pathogens and the immune response of the individual. Neutrophils are the first line of innate cellular defense in periodontal tissues and also important in the initial protection against pathogens. The chemokines especially the interleukin 8 (IL-8) are fundamental for the recruitment and activation of the neutrophils in the periodontal tissues. The bacteria stimulate the production of IL-8 in different cells, which are derivative of the periodontal tissues in vitro and in patients with periodontitis. Several mechanisms of intracellular signaling bring to the production of IL-8. Among the periodontal pathogens there are differences in the stimulus for the production of this cytokine: Fusobacterium sp, Actinobacillus actinomycetemcomitans, and some Treponemas always induce their production. Porphyromonas gingivalis and Treponema denticola also stimulate production, but they present mechanisms that can induce quick degradation of this cytokine. The proteases from Porphyromonas gingivalis and the presence of antibodies against the IL-8 can explain the variations in the level of this cytokine in patients with periodontitis and probably in the function of the neutrophils in different aggressive periodontitis. This article reviews the production of IL-8 by several cell populations, in periodontal tissues and crevicular fluids and its role as a clue molecule in immune and inflammatory response.